The sociology of law in the context of Islamic Legal Scholarship in Indonesia - Pradana Boy ZTF (Universitas Negeri Yogyakarta, 2022)
This article examines the sociology of law in the context of Islamic legal scholarship in Indonesia. As a method, the sociology of law has basically been employed by Islamic legal scholars in Indonesia. However, the study of Islamic law is generally under the discipline of Islamic studies. In fact, although Islamic studies in Indonesia has recently utilised social sciences methods, the popularity of this approach is low compared to normative and textual types of Islamic legal studies. In addition, the trend of positivism which has been a general feature of Islamic legal studies has significantly contributed to this situation. In the light of this context, this article offers a view that the adoption of the sociology of law in the context of Islamic legal studies scholarship in Indonesia will serve as an alternative. It is expected that Islamic legal studies will be more multidisciplinary in nature and be based on more tacit social realities in substance.